Genetic variation of Amaranthus retroflexus L. and Chenopodium album L. (Amaranthaceae) suggests multiple independent introductions into Iran - Hamidzadeh Moghadam, Shiva; Alebrahim, Mohammad Taghi; Mohebodini, Mehdi; MacGregor, Dana R. (Frontiers in Plant Science, 2023)
Amaranthus retroflexus L. and Chenopodium album ‎L. ‎‎(Amaranthaceae) ‎are weedy plants ‎that cause ‎severe ecological and economic damage. In this ‎study, we collected‏‎ DNA‎‏‎ from ‎three ‎different countries‎ and assessed genetic diversity using inter-‎simple sequence repeat ‎‎(ISSR) markers. Our analysis shows both weed species have low genetic ‎diversity within ‎a ‎population and high genetic diversity among populations, as well as a low value of gene ‎flow ‎among the populations. ‎UPGMA ‎clustering and principal ‎coordinate analysis indicate four ‎distinct groups for ‎A. retroflexus L. and C. ‎album L. exist. We detected significant isolation-‎by-distance for A. retroflexus L. and no significant correlation for C. ‎album L. These ‎conclusions are based data from 13 ISSR primers where the average percentage of ‎polymorphism produced was 98.46 % for A. ‎retroflexus L. and 74.81% for C. album L‎.‎‏ .‏These ‎data suggest that each population was independently introduced to the location from which it ‎was sampled and these noxious weeds come ‎armed with considerable genetic variability ‎giving them the opportunity to manifest myriad traits that could be used to avoid ‎management ‎practices. Our results, albeit not definitive about this issue, do not support the ‎native status of C. album L. in Iran.‎